The Role of PUSPAGA in Preventing Bullying in Children - Rahayu, Bella Agustina; Sapphira, Tengku Ananda; Casiavera, Casiavera (PT FORMOSA CENDEKIA GLOBAL, 2023)
This research discusses bullying behavior in children. The aim of this research is to determine efforts to prevent bullying among children in Tanjungpinang City. In this research, the method used is a qualitative research method. To find data in this research, interviews were conducted with PUSPAGA regarding efforts to prevent bullying among children which is rampant in Tanjungpinang City. So that prevention efforts are provided to minimize the occurrence of bullying in children. Bullying behavior can have negative impacts on children, such as mental disorders, trauma, not wanting to go to school because they are afraid of being bullied, and physical injury. The many problems regarding bullying behavior that occur among children is proof that there is still a lot of bullying occurring among children. So this research discusses cases of bullying that occur at a child's age.